Developing basic literacy among Chinese schoolchildren through arts education integration: a quarter-century review - Beibei, Zhao; Yuryeva, Kateryna (Professional Art Education, 2025)
Object. The aim of this study is to review the outcomes of the educational policy implemented by the People’s Republic of China in the 21st century, aimed at fostering basic literacy among the younger generation within the framework of the compulsory nine-year education system, particularly through the integration of arts education.Methods. The research methodology is based on the analysis and comparison of a wide range of sources, including regulatory state documents governing the functioning of the education system in the People’s Republic of China – documents from the State Council, the Central People’s Government, and the Ministry of Education of the PRC; various generations of Chinese educational standards, including those focused on the arts (2001, 2011, 2022); materials from international organizations such as UNESCO, OECD, and The World Bank; statistical data from the National Bureau of Statistics of China and the Global Economic Monitor; results from international educational assessments (PISA) and rankings (World University Rankings); the global scientific ranking Nature Index; content from scientometric platforms such as Nature and Web of Science; publications in scientific and pedagogical journals from China and Ukraine; and content from specialized websites. To analyze, compare, and synthesize the extensive statistical data, research findings, and rankings, the authors also created analytical tables and diagrams.Results. A comparison of recent Nature Index data reveals that among the top twenty leading countries, only the People’s Republic of China demonstrates consistent growth in the influence of its scientific publication activity, which serves as an indicator of the effectiveness of the country’s research efforts. A comparison of the 2024 and 2025 indicators shows that the pace of this growth is accelerating. Analysis of the results from the PISA international educational assessment and the World University Rankings over several years supports the conclusion that the course adopted by the PRC at the beginning of the 21st century to reform compulsory nine-year education through integration has proven to be fully justified. Moreover, today’s young scientists and students – those who are securing high positions for Chinese science and education in international rankings – are precisely the individuals who have passed through this renewed and reformed Chinese school system.Conclusions. The study confirms that the broad integration of the arts into school education has contributed to the cultivation of a new generation of the country’s intellectual elite. For instance, science as a pursuit of new knowledge about the world is impossible without creativity, the courage to innovate, openness to diverse perspectives, attentiveness and focus, determination in achieving results, overcoming obstacles, and solving problems. It is precisely these essential personal qualities that are nurtured through engagement with the arts and artistic activities, which the younger generation of Chinese citizens has been exposed to from early childhood in various integrated forms.
Keywords: People’s Republic of China; education; integrative approach; science; ranking; research; arts